Shark control records hindcast serious decline in dugong numbers off the urban coast of Queensland and Dugong distribution and abundance in the southern Great Barrier Reef Marine Park and Hervey Bay: results of an aerial survey in October-December 1999 - Marsh, H.; De'ath, G.; Gribble, N.; Lane, B.; Lawler, I.R. (Great Barrier Reef Marine Park Authority, 2001)
This technical report consists of the reports of two of the studies commissioned by the Great Barrier Reef Marine Park Authority: 1. Shark control records hindcast serious decline in dugong numbers off the urban coast of Queensland by Helene Marsh, Glenn De'ath, Neil Gribble and Baden Lane. 2. Dugong distribution and abundance in the southern Great Barrier Reef Marine Park and Hervey Bay: results of an aerial survey in October-December 1999 by Helene Marsh and Ivan Lawler.
Keywords: Mammal populations; Dugong; Aerial surveys; Vulnerability; Environmental management; Scientific research; Animals; Research; Reef Ecosystems and Species; Managing Multiple Use